Food rack project / Muhammad Irsyad Fakruddin Mohd Nasir - Mohd Nasir, Muhammad Irsyad Fakruddin (2022)
This study investigated how to design and provide solutions for any daily issue using the mechanical engineering design process. Many people who are troubled physically with issues like not having enough space in their rooms to store their food or other items, so people buy shelves or racks to solve their problems, such as not having enough room in their rooms to keep their food or other belongings. The objective for this project is to help student who lives in dorm/campus and housewives to save a lot of space and making it easier for them to manage their belongings and food.